“Краткое руководство к красноречию” М. В. Ломоносова: история первого издания (1748 г.) - Костин, Андрей Александрович; Лемешев, Константин Николаевич (2017)
The article studies the first editions of Mikhail Lomonosov’s “Kratkoe rukovodstvo k krasnorechiiu (A Short Manual in Rhetoric),” issued by the Academy of Sciences in 1748 and 1765. The textual variations help us demonstrate that the common view on the history of these texts as directly descending from the only extant set of proof-reads is false. With textual and codicological analysis (including the presentation of three unique copies of the first edition), and using the records of the Academy Chancellery and Typography, we argue that the creation of the unique varying copies of the first edition were caused not only by the fire in the Academy building (December 5, 1747), but also by the lack of paper in the Typography’s stock and the fact, that the most part of the book had not yet been written by the time it started to print. For more than a year Lomonosov provided the typography with only small portions of the text, and thus the reprinting the portion of the print run damaged by the fire coincided with the creation of the last chapters. This made it possible for Lomonosov to radically rewrite the first paragraphs of an early chapter “On fictions,” turning it into a theoretical text, legitimizing the fiction genres, which became the crucial part of the Academy print in 1747/48 (Volchkov’s translation of the Aesop’s Fables; the translations of the Fenelons’ Telemaque and Barclay’s Argenis; Sumarokov’s tragedies). The article concludes with a verified stemma of the print sources of the “Kratkoe rukovodstvo,” issued during Lomonosov’s lifetime; and the Moscow edition (1759–1765) is argued to present the latest authorized text.